2013
DOI: 10.5539/ass.v9n4p14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Malaysian Retail Service Quality

Abstract: In retailing different requirement of service quality in product or services environment required. Some of the retail stores have lack on service quality whereas the salesperson is not well trained, unknowledgeable and rude. This study aims to evaluate the retail service quality from a supermarket in Kuching, Malaysia and sets out to determine what influence customers to shop. This research looks at the five dimensions of retail service quality: the physical aspect, reliability, personal interaction, problem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As expected, twenty-eight items loaded on five factors (eigenvalues > 1.0, all cross-loadings < 0.3), namely personal interactions (9 items), store policy (5 items), physical aspects (6 items), reliability (5 items) and problem solving (3 items). This structure perfectly matches the five dimensions of the RSQS, which is developed by Dabholkar et al (1996) and tested in a study of Ibrahim et al (2013).…”
Section: Dimensions Of Retail Service Qualitymentioning
confidence: 59%
See 1 more Smart Citation
“…As expected, twenty-eight items loaded on five factors (eigenvalues > 1.0, all cross-loadings < 0.3), namely personal interactions (9 items), store policy (5 items), physical aspects (6 items), reliability (5 items) and problem solving (3 items). This structure perfectly matches the five dimensions of the RSQS, which is developed by Dabholkar et al (1996) and tested in a study of Ibrahim et al (2013).…”
Section: Dimensions Of Retail Service Qualitymentioning
confidence: 59%
“…For example, an examination of Malaysian supermarket customers supports five factors of the scale (Ibrahim et al, 2013). Other studies have adapted and extended the RSQS in different contexts.…”
Section: Retail Service Qualitymentioning
confidence: 99%
“…The findings indicated that personal interaction and trustworthiness was the most influential service quality indicator. Moreover, (Vazquez et al, 2001); (Ahmad, Ihtiyar, & Omar, 2014); (Ibrahim et al, 2013) also analyzed service quality by using the same indicators. According to the prior studies, the indicators of the retail service quality scale were more extensive in capturing service quality in retailing stores compared to SERVQUAL indicators used in companies that offer services in general (Vazquez et al, 2001).…”
Section: Service Quality In Modern Grocery Storesmentioning
confidence: 99%